Understanding bladder cancer risk: Mendelian randomization analysis of immune cell and inflammatory factor influence - Un, Hiocheng; Wusimanjiang, Wumier; Zhan, Wenhao; Zhang, Xinxin; Li, Minghao; Lei, Jiahao; Lin, Renxuan; Zhang, Yuliang; Chen, Junxing; Wang, Zongren (Frontiers in Immunology, 2024)
The complex roles of immune cells and inflammatory factors in cancer, particularly their association with bladder cancer risk, remain insufficiently understood. This study aims to elucidate potential causal relationships between these elements and bladder cancer development using genome-wide association study (GWAS) summary statistics for 731 immune cell phenotypes and 91 circulating inflammatory factors (cases=2,053; controls=287,137). Our primary analytical approach was Inverse Variance Weighting (IVW), complemented by MR-Egger regression, weighted median, and weighted mode analyses. Sensitivity analyses included Cochran Q test, MR-Egger intercept test, and Leave-one-out test. The findings indicate that monocytes are positively correlated with an increased bladder cancer risk. Conversely, double-negative (DN) T cells, HLA DR+CD8br, and CD28 on CD28+CD45RA+CD8br T cells showed an inverse correlation, suggesting possibly a protective effect. Additionally, inflammatory factors IL-20, IL-22RA1, and Eotaxin were significantly associated with an increased risk of bladder cancer. These results suggest that specific immune cell phenotypes and inflammatory factors might play a role in bladder cancer development and could serve as potential biomarkers for tumor risk assessment. The findings also provide new insights into the pathogenesis of bladder cancer, warranting further investigation.